2001
DOI: 10.1046/j.1365-2893.2001.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of cytomegalovirus DNA in infantile hepatitis

Abstract: We used a PCR method to develop a diagnostic assay for the detection of cytomegalovirus (CMV) DNA in infantile hepatitis, which has been suggested to be associated with CMV infection. CMV DNA was detected in 25 (58.1%) of 43 patients with elevated serum alanine aminotransferase (ALT) levels but no jaundice, and no hepatitis B or C as assessed by conventional PCR. None of the samples from 97 healthy infants tested positive for CMV DNA. We assayed CMV DNA quantitatively in blood using a real-time PCR system that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
3
11
0
1
Order By: Relevance
“…In one study, the CMV DNA was detected in the plasma specimens of four (15.4%) of twenty-six children (median age, 7 months old) with hepatitis, compared with none of the 48 normal control infant (median, 10.5 months) [3]. In another study, the detection rate of CMV DNA in whole-blood samples of 43 infants (mean age 4.6 months) with hepatitis was 58.1% by conventional PCR assay and 67.4% by RT-PCR assay, respectively [2]. In contrast, no CMV DNA was detected in any of the 97 healthy subjects (mean age 6.3 months) which was statistically significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In one study, the CMV DNA was detected in the plasma specimens of four (15.4%) of twenty-six children (median age, 7 months old) with hepatitis, compared with none of the 48 normal control infant (median, 10.5 months) [3]. In another study, the detection rate of CMV DNA in whole-blood samples of 43 infants (mean age 4.6 months) with hepatitis was 58.1% by conventional PCR assay and 67.4% by RT-PCR assay, respectively [2]. In contrast, no CMV DNA was detected in any of the 97 healthy subjects (mean age 6.3 months) which was statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…CMV infection is the main cause of non A-E viral Pediatr Gastroenterol Hepatol Nutr infantile hepatitis. A Japanese study [2] demonstrated that CMV DNA was detected in whole-blood samples of twenty-five (58.1%) of 43 infants (mean age 4.6 months) with hepatitis. Another Japanese study [3] showed that the DNA of CMV was detected in the plasma of six (23%) of 26 infants (median, 7 months old; range, 1 to 24 months).…”
Section: Introductionmentioning
confidence: 99%
“…CMV infection is one of the main causes of neonatal and infantile hepatitis (5)(6)(7)23), but confirmation of the association of CMV infection with hepatitis is sometimes difficult. Primary CMV infection is typically determined by the detection of serum anti-CMV IgM antibody or the seroconversion of IgG antibody.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports describing the frequency of the association of CMV with infantile hepatitis. Funato et al (7) reported that CMV DNA was detected in blood from 58% of infants with elevated serum ALT. In the present study, six of 26 infants (23%) were positive for CMV DNA.…”
Section: Discussionmentioning
confidence: 99%
“…CMV sometimes causes neonatal and infantile hepatitis, and also causes CMV-induced mononucleosis in children and adolescents [7]. We report a 16-year-old boy with prolonged hypertransaminasemia after CMV hepatitis,most likely related to NASH, associated with obesity.…”
Section: Introductionmentioning
confidence: 88%